Study on the Analytical Behaviour of Concrete Structure Against Local Impact of Hard Missile - Ahmad Zaidi, Ahmad Mujahid; Abdul Rahman, Ismail; Latif, Qadir Bux alias Imran (International Journal of Sustainable Construction Engineering and Technology, 2011)
Concrete is basic construction material used for almost all kind of structure. However, in the majority essential structures such as nuclear plants, Power plants, Weapon Industries, weapons storage places, water retaining structures like dams, highways barriers, bridges, & etc., concrete structures have to be designed as self-protective structure which can afford any disaster or consciously engendered unpleasant incidents such as incident occurs in nuclear plants, incident in any essential industry, terrorist attack, Natural disasters like tsunami and etc missile attack, and local impact damage generated by kinetic missiles dynamic loading (steel rods, steel pipes, turbine blades, etc.). This paper inquisitively is paying attention on verdict of the recent development in formulating analytical behavior of concrete and reinforced concrete structures against local impact effect generated by hard missile with and without the influence of dimensional analysis based on dominant non-dimensional parameters, various nose shape factors at normal and certain inclined oblique angles. The paper comprises the analytical models and methods for predicting penetration, and perforation of concrete and reinforced concrete. The fallout conquer from this study can be used for making design counsel and design procedures for seminal the dynamic retort of the concrete targets to foil local impact damage.